PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN (Studi Kasus pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Alendra Taufiqurrahman; Marsono Marsono (Diponegoro Journal of Accounting, 2025)
This study aims to determine the effect of intellectual capital on financial performance in banking sector companies listed on the Indonesian Stock Exchange (IDX) in the period 2019 to 2022. Intellectual capital in this study is proxied by capital employed, human capital, and structural capital while the company’s financial performance is proxied by net profit margin (NPM) and return on investment (ROI).This study population consists of all banking sector companies listed on the Indonesian Stock Exchange (IDX) in the period 2019 to 2022. The sample was obtained using a purposive sampling method based on predetermined criteria. The type of data is secondary data using the company’s financial reports and the official IDX website. Data were obtained using the documentation method and processed using the multiple linear regression analysis method.The results of the study show that human capital and structural capital only have a significant effect on NPM and do not have a significant effect on ROI because the significance value obtained for NPM is smaller than the alpha value and the significance value for ROI is greater than the alpha value. Meanwhile, the significance value of capital employed is smaller than the alpha value so that capital employed does not have a significant effect on either NPM or ROI